Implementasi KIP Kuliah Pada Mahasiswa/I Universitas Palangkaraya - Ringgo Saprianto; Puput Iswandyah Raysharie; Alexandra Hukom; Dedi Takari (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
In summary, this research aimed to investigate the implementation of the KIP-K program at Palangkaraya University. The author used a qualitative approach with primary data types and analyzed the data using descriptive processed data from a Likert scale questionnaire. The findings revealed that the use of the KIP-K program was considered very useful, particularly in the field of education for those who are still incapable of fulfilling their needs. However, the study also identified some obstacles in terms of submitting requirements, which may hinder the implementation of the program. Overall, the implementation of the KIP-K program at Palangkaraya University was found to be going well. To improve the program's effectiveness, the author suggested that more focused efforts are needed to socialize the program and provide clearer and more accessible information to all students who meet the program's requirements.